Estimating the future global dose demand for measles–rubella microarray patches - Ko, Melissa; Malvolti, Stefano; Cherian, Thomas; Mantel, Carsten; Biellik, Robin; Jarrahian, Courtney; Menozzi-Arnaud, Marion; Amorij, Jean-Pierre; Christiansen, Hans; Papania, Mark J.; Meltzer, Martin I.; Masresha, Balcha Girma; et al. (Frontiers in Public Health, 2023)
Background: Progress towards measles and rubella (MR) elimination has stagnated as countries are unable to reach the required 95% vaccine coverage. Microarray patches (MAPs) are anticipated to offer significant programmatic advantages to needle and syringe (N/S) presentation and increase MR vaccination coverage. A demand forecast analysis of the programmatic doses required (PDR) could accelerate MR-MAP development by informing the size and return of the investment required to manufacture MAPs. Methods: Unconstrained global MR-MAP demand for 2030-2040 was estimated for three scenarios, for groups of countries with similar characteristics (archetypes), and four types of uses of MR-MAPs (use cases). The base scenario 1 assumed that MR-MAPs would replace a share of MR doses delivered by N/S, and that MAPs can reach a proportion of previously unimmunised populations. Scenario 2 assumed that MR-MAPs would be piloted in selected countries in each region of the World Health Organization (WHO); and scenario 3 explored introduction of MR-MAPs earlier in countries with the lowest measles vaccine coverage and highest MR disease burden. We conducted sensitivity analyses to measure the impact of data uncertainty. Results: For the base scenario (1), the estimated global PDR for MR-MAPs was forecasted at 30 million doses in 2030 and increased to 220 million doses by 2040. Compared to scenario 1, scenario 2 resulted in an overall decrease in PDR of 18%, and scenario 3 resulted in a 21% increase in PDR between 2030-2040. Sensitivity analyses revealed that assumptions around the anticipated reach or coverage of MR-MAPs, particularly in the hard-to-reach and MOV populations, and the market penetration of MR-MAPs significantly impacted the estimated PDR. Conclusions: Significant demand is expected for MR-MAPs between 2030-2040, however, efforts are required to address remaining data quality, uncertainties and gaps that underpin the assumptions in this analysis.